ANALYSIS OF INTERPERSONAL METAFUNCTION IN MENGKET RUMAH MBARU TRADITION KARONESE SOCIETY - Alemina Br Perangin-angin; Robert Sibarani (Universitas Islam Sumatera Utara (UISU), 2018)
Karonese mengket rumah mbaru tradition is a ceremony to thank God and to share happiness to the relative and friends because one manages to build his own house. Karonese has a community kinship system named merga si lima, rakut si telu, perkadekaden sisiwah tambah sada. All of them have different functions in mengket rumah mbaru tradition. There is one part of mengket rumah mbaru ceremony that all of them give some kind speech to the host. This research try to find out interpersonal metafunction meaning in the mengket rumah mbaru traditionis. This research employs descriptive qualitative to analyze interpersonal meaning performed in the ceremony by studying the utterances by anak beru, kalimbubu and senina during in one part of the ceremony. The researcher directly involves in this ceremony to observe all the data. Theory of interpersonal meaning proposed by M.A.K Halliday is applied to analyze and classify the mood auxiliary, personal pronoun in pronoun system. The finding informed that mood positive declarative appears 88,4%. Imperative appear 10.1 %, negative declarative 0%. There are 25 modal verbal found in the ceremony, “will 52% must 16%, can 32% 0%. Personal pronoun “we” 60%, you 24, it =9, she3%, he 4%. Tenses shift future 60%, present tense 40%, and past 10%.